A compact stub‐loaded composite right/left‐handed resonator and its application in bandpass filters. Issue 9 (September 2015) - Xu, Kai‐Da; Zhang, Yong‐Hong; Li, Xue‐Shi; Ai, Jing; Fan, Yong; Joines, William T.
ABSTRACT A new compact stub‐loaded composite right/left‐handed (SL‐CRLH) resonator is presented for the first time. The resonance properties of the proposed SL‐CRLH resonator are deduced by odd‐ and even‐mode analysis method. Besides miniaturization and wide upper stopband, the bandpass filter (BPF) using SL‐CRLH resonator is found to have an additional advantage that the bandwidth can be tuned by the stub length. Based on the proposed resonator, two BPFs operating at 3.1 GHz with source‐load magnetic cross coupling are designed, fabricated, and tested. The good agreements between simulated and measured results validate the design concept. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1999–2002, 2015